2008
DOI: 10.1177/0091270007313327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Food, Type of Food, and Time of Food Intake on Deferasirox Bioavailability: Recommendations for an Optimal Deferasirox Administration Regimen

Abstract: Deferasirox (ICL670) is representative of a new class of tridentate iron chelators, formulated as tablets for dispersion. Deferasirox has exhibited high potency and a clinically manageable safety profile in preclinical models and in an extensive clinical program. The effect of food and time of food intake on the pharmacokinetics of deferasirox was investigated in healthy volunteers and patients with transfusional hemosiderosis. The bioequivalence of a single oral dose of deferasirox (20 mg/kg) was assessed fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 22 publications
3
25
0
1
Order By: Relevance
“…The absence of correlation between DFX plasma Ctrough and dose, as shown in Fig. 4, substantiates the prediction of an high inter individual variability in pK, as shown by recent phase II studies observations [8], [15] and [26]. The negative correlation, instead, observed between DFX plasma Ctrough and patients ferritin concentrations (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The absence of correlation between DFX plasma Ctrough and dose, as shown in Fig. 4, substantiates the prediction of an high inter individual variability in pK, as shown by recent phase II studies observations [8], [15] and [26]. The negative correlation, instead, observed between DFX plasma Ctrough and patients ferritin concentrations (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The LOQ (0.15625 μg/ml) of the developed assay makes methodology suitable to perform DFX therapeutic monitoring in thalassaemic treated patients. DFX values obtained from plasma of patients resulted in the expected range of concentrations according to available literature data [8], [15] and [26]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…haematologica | 2013; 98(1) food on drug absorption, 44 ineffective erythropoiesis, splenectomy 45 and overall iron burden, contribute to such variability. In 2008, Cohen et al showed that the rate of transfusion correlates with the effectiveness of DFX and DFO.…”
mentioning
confidence: 99%
“…For this reason the drug must be taken at least 30 minute before eating, preferably at the same time every day. 41 The patient age is another parameter influencing the bioavailability which is lower for the adolescents (12-17 years old) and children (2-12 years old).…”
mentioning
confidence: 99%